A combined fleet size and mix vehicle routing model for last-mile distribution in disaster relief - Katharina Eberhardt; Florian Diehlmann; Markus Lüttenberg; Florian Klaus Kaiser; Frank Schultmann (Progress in Disaster Science)
Disasters pose a significant challenge for last-mile operations, straining emergency logistics systems' ability to provide efficient aid and support. In this context, a Fleet Size and Mix Vehicle Routing Problem for Disaster Management (FSMVRP-DM) is formulated, incorporating a fleet composition decision tailored to the specifics of disaster relief logistics. The model aims to optimize routing and analyze fleet decisions to minimize the sum of operating costs and population deprivation costs. Moreover, a prioritization approach is introduced to monitor deprivation time during transport resource scarcity, adjusting routes periodically to prevent extended supply gaps and minimize suffering costs. In addition, a case study is conducted in the German state of Baden-Württemberg to illustrate the potential applicability of the model. The findings highlight the advantages of integrating diverse and innovative fleet types, such as drones, and prioritizing the supply of multiple demand points when resources are scarce. Overall, the research offers decision support for authorities by enhancing information transparency, facilitating resource management, strengthening the effectiveness of disaster response capabilities, and providing resilient and adaptive strategies for last-mile distribution.